Synthesis, Structure And In Vitro Anticancer Studies Of Dinuclear Silver(I)-N-Heterocyclic Carbene Complexes Derived From Xylyl Linked Bis-Benzimidazolium Salts - Iqbal, Muhammad Adnan (2014)
The current study was aimed to synthesize three series of bisbenzimidazolium salts (12-44) as stable N-heterocyclic carbene (NHC) precursors and their complexation with silver(I) ions in order to obtain dinuclear silver(I)-NHC complexes (45-77). Each series of salts was derived either from para-, meta-, or ortho-xylene linked systems having ethyl-decyl, benzyl and i-propyl substituents at number 3-position of benzimidazolium ring. The salts and complexes were characterized by spectroscopy (FT-IR, 1H and 13C NMR), elemental analysis (CHN) and single crystal X-ray diffraction techniques. All the complexes were prepared by in situ reaction of Ag2O with the corresponding bis-benzimidazolium salts and were tested against human colon cancer cells. Selected salts (12-14, 18-20, 21) and respective complexes (45-47, 29-31, 54) were further tested against acute promyelocytic leukaemia and immortalized myelogenous leukaemia cells. The compounds showed potential anticancer activity against all the tested cancer cell lines. Moreover, complexes exhibited higher cytotoxicity compared to respective salts. The anticancer potential of compounds increased with the increase in chain length at position 3-nitrogen. Furthermore, considering the triangular relationship among cancer, inflammation and oxidation, selected compounds were further tested for possible anti-oxidant and anti-inflammatory activities. The tested compounds did not show anti-oxidant behaviour however, proved to have anti-inflammatory activity comparable to the standards used.